Fifth IEEE International Conference on Data Mining (ICDM'05)
DOI: 10.1109/icdm.2005.127
|View full text |Cite
|
Sign up to set email alerts
|

Segment-Based Injection Attacks against Collaborative Filtering Recommender Systems

Abstract: Significant vulnerabilities have recently been identified in collaborative filtering recommender systems. Researchers have shown that attackers can manipulate a system's recommendations by injecting biased profiles into it. In this paper, we examine attacks that concentrate on a targeted set of users with similar tastes, biasing the system's responses to these users. We show that such attacks are both pragmatically reasonable and also highly effective against both user-based and itembased algorithms. As a resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 5 publications
1
77
0
Order By: Relevance
“…The main aim of the attacker is to interact with the RS to build a large number of fake user profiles in the system with the target of affecting the system output i.e. either push (promote) or nuke (demote) a particular item [7]. Previous work done on has shown that if recommender systems of e-commerce are not protected from these attacks, there is a very high risk that the trust of customers in the site and predictions can be affected by the attacker.…”
Section: Introductionmentioning
confidence: 99%
“…The main aim of the attacker is to interact with the RS to build a large number of fake user profiles in the system with the target of affecting the system output i.e. either push (promote) or nuke (demote) a particular item [7]. Previous work done on has shown that if recommender systems of e-commerce are not protected from these attacks, there is a very high risk that the trust of customers in the site and predictions can be affected by the attacker.…”
Section: Introductionmentioning
confidence: 99%
“…Our prior work [2,3] identified a number of attack models, based on different assumptions about attacker knowledge and intent. The overall conclusion is that an attacker wishing to "push" a particular product (make it more likely to be recommended) or to "nuke" it (make it less likely to be recommended) can do so with a relatively modest number of injected profiles, with a minimum of system-specific knowledge and with only the kind of general knowledge about likely user ratings distribution that one might find by reading the newspaper.…”
Section: Introductionmentioning
confidence: 99%
“…These types of attack have been extensively studied as shilling attacks or profile injection attacks. According to such attacks usually involve setting up dummy profiles, and assume different amounts of knowledge about the system [58].…”
Section: The Challenges and Limitations Of Recommendation Systemsmentioning
confidence: 99%